Assessment of the gold nanoparticles biosynthesized using Casuarina equisetifolia bark extract against the ethion induced Hepato- and neurotoxicity in rats - Wael Mahmoud Aboulthana; Noha El-Sayed Ibrahim; Amal Gouda Hussien; Amgad Kamal Hassan; Wagdy K.B. Khalil; Hassan Abdel-Gawad; Hamdy Ahmed Taha; Ayda K. Kelany; Kawkab A. Ahmed (Journal of Genetic Engineering and Biotechnology)
Ethion (Etn) is classified as an organophosphate pesticide (OP) that causes toxicity even at low concentrations and targets the liver, brain, kidney, and blood. Gold nanoparticles (Au-NPs) were biosynthesized from the whole methanolic extract of Casuarina equisetifolia bark, and their efficacy against Etn-induced hepato- and neurotoxicity in rats was assessed. In addition to determining conventional biochemical measurements, the target tissues (liver and brain) were examined for oxidative stress, inflammatory, and fibrotic markers. The protein and isoenzyme patterns were also assayed using an electrophoretic technique. Additionally, apoptotic gene expression was measured. The target tissues were also subjected to histopathological analysis. In all groups treated with C. equisetifolia bark gold nano-extract, it was observed that the levels of the hematological measurements that were impacted by the oral injection of Etn had recovered to normal. Regarding the biochemical measurements, the group that received nano-extract pretreatment showed greater improvement than the therapeutic group. The levels of inflammatory indicators significantly decreased (p ≤ 0.05), while the antioxidant system markers increased in both liver and brain tissues in the group that received the nano-extract beforehand. In both target tissues, especially in the pre-treated group, the nano-extract reduced the severity of the Etn-caused lesions. During electrophoretic assays, the nano-extract in the pre-treated group prevented the qualitative alterations indicated by the lowest similarity index (SI%) values of the Etn-injected group compared to the normal group. The molecular assay showed that the nano-extract reduced the expression of apoptotic genes that were markedly elevated in the Etn-injected rats, but it was unable to return their values to normalcy. The study concluded that in the group that received nano-extract pretreatment, the biochemical, histopathological, physiological, and molecular abnormalities caused by Etn were reduced by the C. equisetifolia bark gold nano-extract.